PROBLEMATIKA PENYALURAN ZAKAT MELALUI UNIT PENGUMPUL ZAKAT (UPZ) MASJID DI MADURA - Imam Buchari (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
The Pensyar Section of the Ministry of Religion of East Java, the zakat section, responded to this so that each mosque formed a UPZ Mosque, especially in the Madura work area. The Pensyar and Baznas Section of Sumenep Regency and the Pensyar Section of Pamekasan Regency also gave instructions to mosques. However, these instructions have not received significant results. Many mosques continue to carry out zakat management activities but there is no coordination either with the Regency Ministry of Religion or with the Regency Baznas. This research uses descriptive qualitative analytical research method at the exploratory stage. Data obtained through observation, interviews, and documentation. To determine the validity of the data, the researchers used a triangulation approach. The results of this study are: The background of the issuance of the Perbaznas is due to the existence of laws or regulations relating to UPZ but not yet detailed. For example, Government Regulation (PP) number 14 of 2014 which requires the establishment of a UPZ but has not been clearly regulated. 2) Problems in the formation of UPZ Mosques in Madura can be categorized, namely, cultural problems, administrative complexity problems, problems with the perception of the lack of public trust in the government or the agency that manages ZIS funds, and the lack of socialization budgets to educate the public, and the problem of low community understanding. 3) The problem of culture can be solved by focusing the UPZ of the mosque to manage zakat maal only. Distribution of zakat fitrah is left as usual. Solving the problem of administrative complexity by collaborating with religious instructors to assist the takmir of the mosque so that they can be independent. The resolution of the perception problem is to increase transparency and accountability. Solving the problem of the lack of socialization budget and low public understanding with government initiatives to take breakthroughs in optimizing the budget for socialization and education.